(3JWhjQ fXe eYdheGJ GdMGSH GdBdj (B:s (3JMdjd hJUeje (B/s - .(3HhQR, ejTGd Ls; (3BOeR, OGajOs; (3ejdR, gGQdGfs; (3YHO GdSdGe, EHQGgje (B((3GdEOGQI(B)s; (3GdOQjfj, eMeO fRjgs ((3GdQjGV (B:s (3eYgO GdEOGQI GdYGeI, EOGQI GdHMhK,s, 1988)
(3HjFI JWhjQ GdfXe(B.s
Keywords: (3JMdjd GdfXe (B((3MGSHGJ EdcJQhfjI(B)s; (3JUeje GdfXe (B((3MGSHGJ EdcJQhfjI(B)s